(untitled) (Advances in Knowledge Representation, 2025)
The editorial introduces the thematic issue of Advances of Knowledge Representation (AKR), focused on the scientific production of the "Use and Management of Information and Knowledge" research line at the Graduate Program in Information Technology, Communication, and Knowledge Management (PPGTICGC) at FUMEC University. Celebrating 10 years of the doctoral program, the edition features articles addressing topics such as information management, innovation, information policies, emerging technologies, and knowledge representation. The works reflect the diversity and relevance of the research conducted, with practical applications in areas such as health, education, technology, and governance. The issue also highlights the importance of scientific research in addressing contemporary challenges and promoting social, economic, and cultural impacts. With contributions from faculty, students, and alumni, the journal establishes itself as a space for innovative and high-impact publications. The editorial invites readers to explore the contributions presented, which provide important insights for advancing information science and knowledge management.